2015
DOI: 10.1016/j.eurpsy.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Psychotropic Use Across Europe: Results From a Large Cross-Sectional, Population-Based Study

Abstract: Women use psychotropic medication consistently more often than men, yet reasons for their use are similar between genders. These differences also appear to be contingent on the specific mental disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
41
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 45 publications
10
41
0
18
Order By: Relevance
“…This is consistent with Carrell et al (2015) and Hylan et al (2015) which both found women to represent about two-thirds of the chronic opioid therapy population in their studies. Overall, higher women's representation is consistent with the notion that women are more likely than men to use psychotropic and opioid medications (31)(32)(33). However, men generally have higher rate of opioid overdose deaths per 100,000…”
Section: Demographicssupporting
confidence: 70%
“…This is consistent with Carrell et al (2015) and Hylan et al (2015) which both found women to represent about two-thirds of the chronic opioid therapy population in their studies. Overall, higher women's representation is consistent with the notion that women are more likely than men to use psychotropic and opioid medications (31)(32)(33). However, men generally have higher rate of opioid overdose deaths per 100,000…”
Section: Demographicssupporting
confidence: 70%
“…Several studies have found AD use to be higher among women, and the increased prescription of ADs in recent decades is especially notable among women. [23][24][25]30,43 The higher level of AD prescribing to women may in part be attributed to the greater consumption of healthcare among women in general. 36,44 Apropos of this, there are studies that show that women are more likely than men to receive a prescription during their medical visits.…”
Section: Discussionmentioning
confidence: 99%
“…22 Similar patterns have been found in other countries. [23][24][25] The explanation for this escalation, especially seen in women, remains unclear, but has sometimes been interpreted as a sign of inappropriate use. 8,9 Nevertheless, despite the widespread use of ADs, depression has repeatedly been shown to be inadequately treated in the general population.…”
mentioning
confidence: 99%
“…The prevalence of antidepressants, in the total study population as well as in all the different ATC groups studied, was higher among women than among men during the 3-month period studied. The overall greater use of antidepressants among women compared to men is well-known [6,40]. However, whether this indicates that women are more depressed than men is hard to confirm.…”
Section: Prevalence Of Antidepressantsmentioning
confidence: 99%